Graves-Basedow disease treated by complementary medicine leading to severe thyrotoxicosis - a case report - Klaudia Sapuła; Jakub Gołacki; Aleksandra Marczak; Michalina Hordejuk; Klaudyna Iwaszko-Sochal (Kazimierz Wielki University, 2022)
Graves' disease is a common cause of hyperthyroidism. Inadequate treatment or non-compliance can lead to serious complications, including thyroid storm.  We present the case of a 22-year-old woman who had been treated with antithyroid drugs (ATD) for almost 7 years, however decided to suspend conventional treatment and turned towards complementary and alternative medicine methods. Following the bioenergotherapist's advice, she began taking Lugol's solution (LS) at a dose of 30 drops per day. After about one month of such therapy, the patient was urgently admitted to the Emergency Department with thyrotoxicosis with a high risk of thyroid storm development. With the implementation of intensive thyrostatic treatment and steroid therapy, euthyroidism was successfully restored.